2016
DOI: 10.1063/1.4944642
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructures of phosphorene and transition metal dichalcogenides for excitonic solar cells: A first-principles study

Abstract: Using the many-body perturbation GW theory, we study the quasiparticle conduction-band offsets of phosphorene, a two-dimensional atomic layer of black phosphorus, and transition-metal dichalcogenides (TMDs). The calculated large exciton binding energies of phosphorene and TMDs indicate that their type-II heterostructures are suitable for excitonic thin-film solar cell applications. Our results show that these heterojunctions have a potential maximum power conversion efficiency of up to 12%, which can be furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 58 publications
9
67
3
Order By: Relevance
“…The lattice constants of monolayer BlueP, MoS 2 , MoSe 2 , WS 2 and WSe 2 were fully optimized and the values are 3.268, 3.164, 3.295, 3.165, 3.295 Å, respectively, which are in consistent with the reported data listed in Supplementary Table S1242627303132. The interlayer lattice mismatches between BlueP and MoS 2 , MoSe 2 , WS 2 and WSe 2 were evaluated to be +3.18%, −0.82%, +3.15% and −0.82%, respectively, which are all in an acceptable range and accessible in experimental synthesis.…”
Section: Resultssupporting
confidence: 83%
“…The lattice constants of monolayer BlueP, MoS 2 , MoSe 2 , WS 2 and WSe 2 were fully optimized and the values are 3.268, 3.164, 3.295, 3.165, 3.295 Å, respectively, which are in consistent with the reported data listed in Supplementary Table S1242627303132. The interlayer lattice mismatches between BlueP and MoS 2 , MoSe 2 , WS 2 and WSe 2 were evaluated to be +3.18%, −0.82%, +3.15% and −0.82%, respectively, which are all in an acceptable range and accessible in experimental synthesis.…”
Section: Resultssupporting
confidence: 83%
“…For example, Deng et al reported that a gate‐tunable P‐N diode based on a P‐type black phosphorus and a N‐type monolayer MoS 2 as a photodetector, which showed a photodetection responsivity of 418 mA W −1 and was much higher than the value of 4.8 mA W −1 for the single black phosphorus phototransistors. Ganesan et al demonstrated theoretically that phosphorene and TMDs heterostructures would be suitable for excitonic thin film solar cell applications. The black phosphorus and MoS 2 vdW heterostructure possessed good piezoelectric effect via the compressive strain .…”
supporting
confidence: 85%
“…It should be mentioned that our calculated absorption coefficients for Si and phosphorene are in accordance with the previous results. 56,57 The three OOHs have remarkably higher absorbance coefficients (10 5 cm − 1 ) than those of Si, phosphorene, and MoS2. Furthermore, their absorptions cover almost the entire incident solar spectrum, which could guarantee high conversion efficiency in terms of utilization of solar energy.…”
Section: As Shown Inmentioning
confidence: 99%